Executive Engineer receives Lifelong Learning Professional Award - Siti Nurfarmy, Ibrahim (2019)
“No pain, no gain”, these words portray the recipient of Lifelong Learning Professional Award, Lim Poh Ann, 53. Although he is bound by his current role as an Executive Engineer, it does not stop him from graduating from the Executive Bachelor in Business Management (Majoring in Industrial Operations) at Universiti Malaysia Pahang (UMP).